PENGARUH ONLINE STORE IMAGE DAN ONLINE CUSTOMER REVIEW TERHADAP KEPUTUSAN PEMBELIAN PRODUK DI TOKOPEDIA: (Survey pada Masyarakat di Kabupaten Kuningan) - Dwi Novita, Alviana; Wachjuni, Wachjuni; Manalu, Vigory Gloriman (FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS KUNINGAN, 2023)
This research aims to determine the influence of online store image and online customer reviews on purchasing decisions for online store products on Tokopedia. By knowing the factors that influence consumer purchasing decisions, companies can get important information to implement better marketing strategies, especially in online media. This research uses descriptive and verification methods with the population being people who have made known Tokopedia transactions in the Kuningan Regency area. The sampling technique used purposive sampling technique with a sample size of 100 people. The data collection technique used in this research is by distributing questionnaires and measuring using an interval scale. Data analysis uses multiple linear regression analysis assisted by SPSS 23 software. Based on the results of research that has been carried out, it shows that: (1) online store image and online customer reviews together have a positive and significant effect on purchasing decisions at Tokopedia, (2) online store image has a positive and significant effect on purchasing decisions at Tokopedia (3) online customer reviews have a positive and significant effect on purchasing decisions at Tokopedia Keywords: Online Store Image, Online Customer Review, Purchasing Decisions.